An Implementation in Image Compression Technique and its Effect on Image - Atulker, Pradeep Kumar; Gupta, Rajendra (International Journal of Computer Sciences and Engineering, 2019)
One of the significant aspects of image storage is its effective compression. The compression is a very important factor of the solutions available for creating file sizes of manageable and transmittable dimensions. In a scattered environment, the big images file remains a major bottleneck within systems. With the increasing in bandwidth by another method, the cost sometimes makes a less attractive solution. The goal of image compression is to reduce the number of bits wanted to represent an image by eliminating the spatial and spectral terminations as much as possible. This paper present the algorithm working behind the image compression and its implementation to achieve maximum possible compression in image without degrading its property. After analysis the results, it is found that the proposed algorithm reduces the image file size upto 86 per cent.